A novel RE Teams selection process for user-centric requirements elicitation frameworks based on big-five personality assessment model - Shah, Asadullah; Iqbal, M. Aqeel (2020)
The requirements elicitation team selection process is considered as the key factor for planning the activities of work tasks performed by the requirements engineering teams. Consequently, the selection of most appropriate requirements elicitation teams for user-centric requirements elicitation frameworks plays a critical role in improving the quality of requirements elicitation frameworks. This paper presents an innovative process for requirements elicitation team’s selection for user-centric requirements elicitation frameworks. The presented process uses big-five personality assessment model to select the most appropriate requirements elicitation teams for such frameworks. The presented team selection process takes input from the software development industry data advertised for the induction of requirements analysts and computes the most relevant big-five personality traits for requirements engineering teams. The big-five personality traits predicted by the proposed process have been benchmarked with the predictions of the already available processes. The results obtained by using the proposed process have been found substantially improved to better support the requirements engineering works.